Scalable Processing Ultrathin Polymer Dielectric Films with a Generic Solution Based Approach for Wearable Soft Electronics. Issue 7 (12th April 2019) - Chen, Sujie; Peng, Sai; Sun, Wenjian; Gu, Guoying; Zhang, Qing; Guo, Xiaojun
Abstract: Wearable intelligence on human body requires light and soft electronics built on ultrathin supporting films. It would be ideal to have a generic and scalable approach for processing such ultrathin electronics based on various materials to accommodate different design requirements. In this work, a solution based delamination approach is developed using sodium hydroxide (NaOH) treated cross‐linked polymethylmethacrylate (c‐PMMA) film as the separation layer to process ultrathin polymer films. The c‐PMMA layer has resistance to various solvents for coating different polymer materials on top. Reaction of the c‐PMMA surface with mixture of NaOH and water reduces adhesion between the polymer film and the carrier substrate. The polymer film is thus able to be delaminated with facile processes. The approach is applied to fabricate ultrathin flexible or stretchable transparent conductive films, and resistive strain sensors using different polymer materials. A new wrinkle structure capacitive pressure sensor is also realized by integrating different ultrathin polymer films, and presents higher or comparable sensitivity (2.76 kPa −1 ) compared to previous work but with a much lighter weight (<60 g m −2 ). Wearable systems using these sensors are finally built for real time measuring wrist pulse waves, and controlling all actions of a shooting computer game with only three fingers. Abstract : A solution based delamination approach is developed using sodium hydroxide (NaOH) treated cross‐linked polymethylmethacrylate (c‐PMMA) film to accelerate the separation between the ultra‐thin conductive polymer films and the substrate surface. Flexible pressure and strain sensors based on the fabricated ultra‐thin films were demonstrated for wearable applications.